PENGARUH PEMBERDAYAAN DAN KETERLIBATAN KERJA TERHADAP KINERJA PEGAWAI - Nurwiah Bahrin; Patwayati Patwayati; Nasrul Nasrul (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2017)
The purpose of this study was to determine the effect of empowerment and work involvement on employee performance at the Konawe District Forest Service. A total of 48 employees became respondents using census research spread across all rooms in the Konawe District Forest Service. Data were analyzed by multiple regression analysis through the SPSS for Windows program.The results showed that empowerment and work involvement simultaneously had a significant effect on employee performance with determination of 0.468 or 46.8%. empowerment partially has a positive and significant effect on employee performance, work involvement has a positive and not significant effect on employee performance. It is expected that further research will reconsider other variables that influence employee performance, namely leadership style, work motivation and work environment.Keywords:Empowerment, Work Involvement and Employee Performance